An efficient "Ratiometric" fluorescent chemosensor for the selective detection of Hg2+ ions based on phosphonates: its live cell imaging and molecular keypad lock applications. Issue 7 (28th January 2019) - Vinoth Kumar, Gujuluva Gangatharan; Kannan, Ramaraj Sayee; Chung-Kuang Yang, Thomas; Rajesh, Jegathalaprathaban; Sivaraman, Gandhi
Abstract : Herein, we have reported the ability of smart chemosensors (L1 andL2 ) to selectively detect Hg(ii ) ions over other metal ions and examined this phenomenon by various spectroscopy techniques. Abstract : Herein, we have reported the ability of smart chemosensors (L1 andL2 ) to selectively detect g 2+ ions over other metal ions and examined this phenomenon by various spectroscopy techniques. Particularly, the proposed chemosensors exhibited notable color and spectra changes with the addition of mercury ions. Moreover, colorimetry measurements and fluorescence could be reversed with the addition of EDTA into theL1-Hg 2+ andL2-Hg 2+ solutions. Based on the excellent reversibility of this process, we designed a molecular-scale sequential information processing circuit and proposed the "Writing-Reading-Erasing-Reading" and "Multi-write" behaviors in the form of binary logic. Furthermore, L1 andL2 mimic a molecular keypad lock and molecular logic gates with the successive addition of Hg 2+ and EDTA. The binding ability of Hg 2+ ion withL1 andL2 was further demonstrated by density functional theory (DFT) studies. The biocompatibility of these chemosensors was successfully used for live cell imaging of Hg 2+ in HeLa cells under the experimental conditions. Furthermore, the sensorsL1 andL2 were useful in the determination of the concentration of Hg 2+ ions in real water samples; this indicated their potential for practical applications.